PENGEMBANGAN E-MODUL INTERAKTIF BERBASIS ANDROID MENGGUNAKAN ISPRING SUITE PADA PEMBELAJARAN IPAS KELAS V SDN 04 WAWONII UTARA - Nurhasmiati; Zila Razilu; Hendra Nelva (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop an Android-based interactive e-module utilizing iSpring Suite as a learning medium for the Science and Social Studies (IPAS) subject in fifth-grade classrooms at SDN 04 Wawonii Utara. The development of this module is motivated by the growing need for engaging and interactive instructional materials that align with the objectives of the Merdeka Curriculum. The research employed a Research and Development (R&D) approach using the 4D model, which consists of four phases: Define, Design, Develop, and Disseminate. The participants involved in the study included 20 students and 2 subject teachers. Data were collected through expert validation, questionnaires to assess user responses, and pre-test and post-test instruments to evaluate learning outcomes. The results demonstrate that the e- module is highly valid (average score of 91%), highly practical (93%), and effective in enhancing students' academic performance, with an average post-test score of 86.2. These findings indicate that the developed e-module is feasible and appropriate for use as an instructional tool in elementary- level IPAS education.